Up and running Groovy - Kousen, Ken.; Safari eBooks ([Sebastopol, Calif.] : O'Reilly Media, 2011)
"The goal of this screencast is to introduce the Groovy programming language to developers. Groovy is the hottest of the new family of dynamic languages that run on the Java Virtual Machine, and it combines intuitive syntax with many of the advanced features, like closures and metaprogramming, found in modern languages. Since Groovy is very similar in syntax to Java, existing Java developers will find it particularly easy to learn. Any developer familiar with object-oriented programming will find it useful, however."--Resource description page.
Title from title screen.
Publisher's name from resource description page (viewed Apr. 4, 2012).
Presenter, Ken Kousen.
Keywords: Groovy (Computer program language); Java (Computer program language); Object-oriented programming (Computer science); Electronic books